If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(n + -5) + 2 = 5(n + 5) + 2 Reorder the terms: 5(-5 + n) + 2 = 5(n + 5) + 2 (-5 * 5 + n * 5) + 2 = 5(n + 5) + 2 (-25 + 5n) + 2 = 5(n + 5) + 2 Reorder the terms: -25 + 2 + 5n = 5(n + 5) + 2 Combine like terms: -25 + 2 = -23 -23 + 5n = 5(n + 5) + 2 Reorder the terms: -23 + 5n = 5(5 + n) + 2 -23 + 5n = (5 * 5 + n * 5) + 2 -23 + 5n = (25 + 5n) + 2 Reorder the terms: -23 + 5n = 25 + 2 + 5n Combine like terms: 25 + 2 = 27 -23 + 5n = 27 + 5n Add '-5n' to each side of the equation. -23 + 5n + -5n = 27 + 5n + -5n Combine like terms: 5n + -5n = 0 -23 + 0 = 27 + 5n + -5n -23 = 27 + 5n + -5n Combine like terms: 5n + -5n = 0 -23 = 27 + 0 -23 = 27 Solving -23 = 27 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| x^2-7x+16=3x | | -4+9=17 | | 5(x-2)+7=2(x+1) | | (3x)(3xy)+(5x2)(4y) | | 43+2p=24 | | 4x+8y=10 | | 5x+4=-x-10 | | 3*x+y=14 | | 10+x-6x=3+2x | | (5x+4)=(x-10) | | 3y^2+5y=12 | | 2x-6=(-14) | | 5x+4=x-10 | | 5x^2+11x+6=0 | | 3(6p+2)=20 | | 400=2x+x/3 | | 0.5=-0.6c+2.3 | | 4x^3+24x^2-x-6=0 | | 7x-(6x+4)=2 | | 4x+7=7x-8 | | (X-3)(x+5)=15x | | 24x^2+40x+16=0 | | 3x^2-11x-33=7x^2-3x-33 | | 6t-1/6=9 | | √x-8=6 | | 5x+5x+2+8=6x+4+3x | | 4x-2+11x+17=90 | | 6x^2-31x+28=0 | | -2(5s-4)-8=-2(9s+11)-2 | | 18y^2+9y-5 | | 18y^2+9y-5= | | 2a^2+5a+3= |